Physical Characteristics and Chemical Composition of Meat from Sheep Fed with Fermented Straw - E. Suryanto; Z. Bachrudin; L. M. Yusiati; A. Wibowo; B. P. Widyobroto (Buletin Peternakan, 1995)
Abstrak dalam bentuk hard copy